Genome‐wide small noncoding RNA profiling of pediatric high‐grade gliomas reveals deregulation of several miRNAs, identifies downregulation of snoRNA cluster HBII‐52 and delineates H3F3A and TP53 mutant‐specific miRNAs and snoRNAs. Issue 10 (3rd June 2015) - Jha, Prerana; Agrawal, Rahul; Pathak, Pankaj; Kumar, Anupam; Purkait, Suvendu; Mallik, Supriyo; Suri, Vaishali; Chand Sharma, Mehar; Gupta, Deepak; Suri, Ashish; Sharma, B.S.; Julka, P.K.; et al.
<x xml:space="preserve">Abstract</x> Pediatric high‐grade gliomas (HGGs) are highly malignant tumors that remain incurable and relatively understudied. The crucial role of noncoding RNAs (ncRNAs) has been reported in various cancers. However, the study on miRNAs in pediatric HGGs is scant and there is no report till date on the status of other small ncRNAs. Genome‐wide microarray analysis was performed to investigate small ncRNA expression in pediatric HGG (n = 14) and compared to adult glioblastoma (GBM) signature. The validation of miRNAs and small nucleolar RNAs (snoRNAs) was done by real‐time polymerase chain reaction. TP53 and H3F3A mutation‐specific miRNA and snoRNA profiles were generated and analyzed. Pediatric HGGs showed upregulation of miR‐17/92 and its paralog clusters (miR106b/25 and miR‐106a/363), whereas majority of downregulated miRNAs belonged to miR379/656 cluster (14q32). Unsupervised hierarchical clustering identified two distinct groups. Interestingly, Group 2 with downregulated 14q32 cluster showed better overall survival. The miRNAs unique to pediatric HGG as compared to adult GBM were predicted to affect PDGFR and SMAD2/3 pathways. Similarities were seen between pediatric HGG and TP53 mutant miRNA profiles as compared to wild types. Several of H3F3A mutation‐regulated genes were found to be the targets of H3F3A mutant‐specific miRNAs. Remarkably, a significant downregulation of HBII‐52 snoRNA cluster was found in pediatric HGGs, and was specific to H3F3A nonmutants. This is the first genome‐wide profiling study on miRNAs and snoRNAs in pediatric HGGs with respect to H3F3A and TP53 mutations. The comparison of miRNA profiles of pediatric HGGs and adult GBM reiterates the overlaps and differences as also seen with their gene expression and methylation signatures.